Evaluation of Land Suitability for Organic Horticulture Farming in Support of Sustainable Agrarian Governance - Romadhona, Sukron; Puryono, Sri; Mussadun, Mussadun (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: Land compatibility can contribute to the optimization of agricultural land use, because this evaluation is used to determine the most appropriate spatial plan for current and future land use. Identifying the suitability of agricultural land is necessary to adapt to increasing food needs caused by expanding population, environmental pollution and climate change. Therefore, this research was conducted to assess the suitability of snake fruit plants. Various factors were considered in this research, such as rainfall, temperature, nutrient availability (wa), rainfall density (rc), organic carbon (nr), slope, flood hazard (fh) and erosion hazard (eh). The results of the classification of land suitability classes in the Sleman Regency area, in this case, are that snake fruit plants in most areas fall into the criteria for land suitability class S2 or quite suitable. The results are with an area of??42,150 Ha or with a percentage of 73.4% of the land suitability class S2 or Sufficiently Suitable. (Medium Suitable) is land that has quite heavy barriers to maintain the level of management that must be carried out. In the land suitability class S1 or very suitable in the research area with an area of?? 10625 Ha or with a percentage of 18.5, the land suitability class Very Suitable (Very Suitable) is land that has no boundaries. The results of the land suitability assessment, both actual and potential, can be carried out by improving efforts such as improving drainage, adding organic material, planting according to contours, fertilizing. Keywords: Horticulture, Uniformity, Land Suitability, Organic Farming, Snake Fruit